1978
DOI: 10.3171/jns.1978.49.5.0669
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical relationships of the superior cerebellar artery and the trigeminal nerve

Abstract: Comparison and distortion of the trigeminal nerve by a tortuous and elongated superior cerebellar artery (SCA) is postulated to be a frequent cause of trigeminal neuralgia. This theory and the use of operative therapy in which the offending arterial loop is separated from the trigeminal nerve has created a need for more detailed information on the relationship of the SCA and the trigeminal nerve. In order to meet this need, 50 trigeminal nerves and the adjacent SCA were examined in 25 adult cadavers. Twenty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
5

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(86 citation statements)
references
References 4 publications
4
77
0
5
Order By: Relevance
“…Moreover, NVC is a common finding in asymptomatic patients [59], in some TN patients it is contralateral to the pain [60] and, finally, many nerve roots are physiologically in contact with arteries and veins in the skull [61]. In order to make clear the concept of NVC and to study its pathogenetic role, the papers of Hardy and Rhoton [59] and Haines et al [58] are quoted. Hardy and Rhoton bilaterally examined the trigeminal roots in 25 corpses of subjects who never had TN.…”
Section: Is Mvd the Etiologic Treatment For Tn?mentioning
confidence: 99%
“…Moreover, NVC is a common finding in asymptomatic patients [59], in some TN patients it is contralateral to the pain [60] and, finally, many nerve roots are physiologically in contact with arteries and veins in the skull [61]. In order to make clear the concept of NVC and to study its pathogenetic role, the papers of Hardy and Rhoton [59] and Haines et al [58] are quoted. Hardy and Rhoton bilaterally examined the trigeminal roots in 25 corpses of subjects who never had TN.…”
Section: Is Mvd the Etiologic Treatment For Tn?mentioning
confidence: 99%
“…The micro vascular compression theory failed to explain the well recognized group of patients in which there was no compressing vessel seen [13]. In addition, autopsy studies [14] showed a large number of previously asymptomatic patients who had blood vessels adjacent to their cranial nerves. There was also evidence on autopsy of bilateral nerve compression in 20% of cases [14] which is high when compared with the clinical incidence of bilateral trigeminal neuralgia in only 2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autopsy studies [14] showed a large number of previously asymptomatic patients who had blood vessels adjacent to their cranial nerves. There was also evidence on autopsy of bilateral nerve compression in 20% of cases [14] which is high when compared with the clinical incidence of bilateral trigeminal neuralgia in only 2% of cases. There is also the argument of what is to be considered a significant compression [1,13] and the dubious explanation of recurrence of symptoms by veins which were previously coagulated and divided collaterally [13].…”
Section: Discussionmentioning
confidence: 99%
“…As III, IV, V Cranial nerves are closely related to SCA, variant origin of SCA may cause neurovascular compression syndrome.One of the trunks of duplicated SCA may compress the trigeminal nerve root and may cause neuralgia. Microsurgical relationship of SCA with V cranial nerve is important not only for trigeminal neuralgia, but also in possible injury of vessels during rhizotomy and other surgeries on V cranial nerve [14]. The variant origin of SCA can be explained on the developmental basis.…”
Section: Resultsmentioning
confidence: 99%